Adjusting the stiffness of a cell-free hydrogel system based on tissue-specific extracellular matrix to optimize adipose tissue regeneration. Issue 1 (1st March 2023) - Li, Ye; Bi, Xin; Wu, Mengfan; Chen, Xinyao; Zhan, Weiqing; Dong, Ziqing; Lu, Feng
Abstract: Background: Large-area soft tissue defects are challenging to reconstruct. Clinical treatment methods are hampered by problems associated with injury to the donor site and the requirement for multiple surgical procedures. Although the advent of decellularized adipose tissue (DAT) offers a new solution to these problems, optimal tissue regeneration efficiency cannot be achieved because the stiffness of DAT cannot be altered in vivo by adjusting its concentration. This study aimed to improve the efficiency of adipose regeneration by physically altering the stiffness of DAT to better repair large-volume soft tissue defects. Methods: In this study, we formed three different cell-free hydrogel systems by physically cross-linking DAT with different concentrations of methyl cellulose (MC; 0.05, 0.075 and 0.10 g/ml). The stiffness of the cell-free hydrogel system could be regulated by altering the concentration of MC, and all three cell-free hydrogel systems were injectable and moldable. Subsequently, the cell-free hydrogel systems were grafted on the backs of nude mice. Histological, immunofluorescence and gene expression analyses of adipogenesis of the grafts were performed on days 3, 7, 10, 14, 21 and 30. Results: The migration of adipose-derived stem cells (ASCs) and vascularization were higher in the 0.10 g/ml group than in the 0.05 and 0.075 g/ml groups on days 7, 14 and 30. Notably, on days 7, 14 and 30, the adipogenesis of ASCs and adipose regeneration were significantly higher in the 0.075 g/ml group than in the 0.05 g/ml group ( p  < 0.01 or p  < 0.001) and 0.10 g/ml group ( p  < 0.05 or p  < 0.001). Conclusion: Adjusting the stiffness of DAT via physical cross-linking with MC can effectively promote adipose regeneration, which is of great significance to the development of methods for the effective repair and reconstruction of large-volume soft tissue defects.